ReaxFF Readctive Force Field for the Y-doped BaZrO3 Proton Conductor with applications to diffusion Rates for Multigranular Systems - Van Duin, Adri C. T. (2008)
Proton-conducting perovskites such as Y-doped BaZiO3 (BYZ) are promising candidates as electrolytes for a proton ceramic fuel cell (PCFC) that might permit much lower temperatures (from 400 to 600 °C). However, these materials lead to relatively poor total conductivity (∼10-4 S/cm) because of extremely high grain boundary resistance. In order to provide the basis for improving these materials, we developed the ReaxFF reactive force field to enable molecular dynamics (MD) simulations of proton diffusion in the bulk phase and across grain boundaries of BYZ. This allows us to elucidate the atomistic structural details underlying the origin of this poor grain boundary conductivity and how it is related to the orientation of the grains. The parameters in ReaxFF were based entirely on the results of quantum mechanics (QM) calculations for systems related to BYZ. We apply here the ReaxFF to describe the proton diffusion in crystalline BYZ and across grain boundaries in BYZ. The results are in excellent agreement with experiment, validating the use of ReaxFF for studying the transport properties of these membranes. Having atomistic structures for the grain boundaries from simulations that explain the overall effect of the grain boundaries on diffusion opens the door to in silico optimization of these materials. That is, we can now use theory and simulation to examine the effect of alloying on both the interfacial structures and on the overall diffusion. As an example, these calculations suggest that the reduced diffusion of protons across the grain boundary results from the increased average distances between oxygen atoms in the interface, which necessarily leads to larger barriers for proton hopping. Assuming that this is the critical issue in grain boundary diffusion, the performance of BYZ for multigranular systems might be improved using additives that would tend to precipitate to the grain boundary and which would tend to pull the oxygens atoms together. Possibilities might be to use a small amount of larger trivalent ions, such as La or Lu or of tetravalent ions such as Hf or Th. Since ReaxFF can also be used to describe the chemical processes on the anode and cathode and the migration of ions across the electrode-membrane interface, ReaxFF opens the door to the possibility of atomistic first principles predictions on models of a complete fuel cell. © 2008 American Chemical Society.